Efektivitas Layanan Pembayaran Digital Dalam Meningkatkan Pengumpulan Zakat : Studi Kasus Inisiatif Zakat Indonesia Dikota Palembang - Dilan Hasanah; Zuul Fitriani Umari; Abubakar Sidik; Peny Cahaya Azwari (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the effectiveness of digital payment services in increasing zakat collection at Inisiatif Zakat Indonesia (IZI) Palembang. This research uses a qualitative descriptive method through interviews, observations, and documentation. The results show that digital payment services implemented by IZI Palembang are quite effective in increasing the amount of zakat collection, although the number of muzakki fluctuates. Bank transfers remain the most dominant payment method, while the use of QRIS and the ZakatPedia application is not yet stable. The main obstacles include limited digital content creativity and low social media interaction. Improvement efforts are carried out through the use of social media and cooperation with communities; however, these efforts still need to be optimized. Therefore, strengthening digital communication strategies and content management is necessary to enhance zakat collection